Stratifying comatose postanoxic patients for somatosensory evoked potentials using routine EEG. (October 2019) - Fredland, A.; Backman, S.; Westhall, E.
Abstract: Introduction: Multimodal neurological prognostication is recommended for comatose patients after cardiac arrest. The absence of cortical N20-potentials in a somatosensory evoked potential (SSEP) examination reliably predicts poor outcome, but presence of N20-potentials have limited prognostic value. A benign routine electroencephalogram (EEG) may identify patients with a favourable prognosis who are likely to have present N20-potentials. Objective: To investigate whether a routine EEG can identify patients where SSEP is unnecessary to perform. Methods: In a multi-centre trial, comatose patients after cardiac arrest were randomised to a controlled temperature of 33 °C or 36 °C. A routine EEG was protocolised and SSEP performed at the clinicians' discretion, both during normothermic conditions. EEGs were categorised into benign, malignant or highly malignant based on standardised terminology. A benign EEG was defined as a continuous normal-voltage background without abundant discharges. The N20-potentials were reported as absent (bilaterally) or present (bilaterally or unilaterally). Results: Both EEG and SSEP were performed in 161 patients. EEG was performed before SSEP in 60%. A benign EEG was seen in 29 patients and 100% (CI 88–100%) had present N20-potentials. For the 69 patients with a malignant EEG and the 63 patients with a highly malignant EEG, 67% (CI 55–77%) and 44% (CI 33–57%) had present N20-potentials, respectively. Conclusions: All patients with a benign EEG had present N20-potentials, suggesting that SSEP may be omitted in these patients to save resources. SSEP is useful in patients with a malignant or highly malignant EEG since these patterns are associated with both present and absent N20-potentials.